The Role of Gender and Power in Jane Austen's Novels (British Journal of Multidisciplinary and Advanced Studies, 2023)
This research paper examines the intricate interplay of gender and power in Jane Austen's novels. By analyzing the portrayal of characters and their interactions, the paper delves into the nuanced depiction of gender roles and power dynamics in Austen's works. The study explores the constraints imposed on women and the expectations of masculinity within the social contexts of Austen's novels. Additionally, it investigates the influence of social hierarchy, economic power, and patriarchal structures on characters' actions and relationships. Through a comparative analysis of specific novels, such as Pride and Prejudice, Sense and Sensibility, and Emma, common patterns and variations in gender and power dynamics emerge. The findings highlight Austen's keen observation of societal norms and the ways in which they shape individuals' agency and relationships. By elucidating the multifaceted nature of gender and power in Austen's works, this research contributes to a deeper understanding of her enduring literary legacy.